An Analytical Programmed Tool for Improving the Reliability of the Figure-of-8 Walk Test in Inclusive Physical Education - Blavt, Oksana; Lei, Shi; Helzhynska, Tetiana; Pityn, Maryan; Herasymenko, Oleksandr; Vovk, Igor; Prozar, Mykola; Hrebik, Oleh (Physical Education Theory and Methodology, 2025)
Objectives. The purpose of the study was to determine the reliability of the Figure-of-8 Walk Test in inclusive physical education using a newly developed analytical programmed tool. Materials and Methods. The study was conducted at both theoretical and empirical levels. A pedagogical experiment was carried out using the Figure-of-8 Walk Test (F8W). The sample consisted of first-year university students who had sustained war-related injuries, including blast-induced traumatic brain injury (TBI) and blast TBI combined with acoustic trauma. Results. The findings of the study are implemented in the newly developed analytical programmed tool designed to support the execution of the F8W. Its core component is a wireless autonomous data collection system that integrates an inertial measurement unit (IMU), a sensor system supported by a neural network, a processing unit, and a Portenta H7 controller—providing a combination of technological integration and artificial intelligence. The IMU was attached to the participant’s body during the execution of the F8W. In real time, measurements of acceleration, velocity, and position were transmitted via Bluetooth. As the participant moved along the test course, the sensor system – supported by the neural network and processing unit – recorded detailed movement data and transmitted it to the microcontroller platform. The Portenta H7 platform aggregated the test parameters from the IMU and sensor system with flexible activation and data-buffering capabilities. The wireless autonomous data collection system processed the output control data while the participant performed the F8W and displayed the information on a PC interface. Statistical verification of the obtained data confirmed that the analytical programmed tool ensures high reliability and validity of F8W measurements. In contrast, traditional recording methods demonstrated low reliability and validity, primarily due to the influence of the human factor. Conclusions. The study demonstrated that the developed analytical tool for real-time assessment of mobility parameters in students with war-related injuries provides excellent measurement reliability compared to conventional Figure-of-8 Walk Test procedures. The tool offers substantial advantages over traditional methods of manual data recording, enhancing accuracy, objectivity, and reproducibility of F8W performance evaluation.